ALAT MONITORING SUHU DAN DETAK JANTUNG MANUSIA BERBASIS INTERNET OF THINGS MENGGUNAKAN BLYNK - Masthura Masthura; Mulkan Iskandar Nasution; Rajai Sitorus (JOURNAL ONLINE OF PHYSICS, 2023)
The purpose of this research is to create and design a way to monitor temperature and human heart rate based on the Internet of Things using blynk. The process of making an Internet of Things-based human heart rate and temperature monitoring device begins with hardware design by connecting all tools, namely, NodeMCU Esp8266, Base Board, Mlx90614, Max30100, Oled, Led, and Buzzer followed by designing software on Arduino and the blynk application where later the measurement results will be compared with the actual tool commonly used, namely the Tensimeter. Based on previous research conducted by Agung (2019), a heart rate and body temperature measuring instrument was made using the Ds18b20 temperature sensor and the Max30100 sensor with Bluetooth Hc-05 communication with an accuracy of 99.1% on heart rate and 99.4% on body temperature, and previous research conducted by Jarot (2021), heart rate measurements were carried out with a pulse sensor 3 times with an error of 16.7 – 20%, as well as previous research conducted by Muhlis (2019). 2017), measurements of heart rate and body temperature were carried out wirelessly with a pulse sensor using 10 objects with an error of 4.94% and using an LM35 with 10 objects with an error of 1.66%. In this study using 3 different people objects which were measured 3 times for each object. with an average error percentage of 0.91% for body temperature and 2.90% for heart rate. after going through the process of hardware design and software design, we have succeeded in designing a temperature monitoring device and human heart rate that can be monitored remotely using the blynk application and has functioned properly and works according to its function and has the advantage of being easier to monitor because it is based on the Internet of Things in real time and has very accurate accuracy with measuring instruments commonly used compared to previous studies.